Model Dependencies of Cloud-Radiative Heating over the North Atlantic - Sullivan, Sylvia; Voigt, Aiko; Albern, Nicole; Bala, Elzina; Braun, Christoph; Choudhary, Anubhav; Hörner, Johannes; Keshtgar, Behrooz; Lentink, Hilke; Papavasileiou, Georgios (Zenodo, 2022)
See all the uploaded REAME ccf_data – cloud-controlling factor data; for the various simulations, histogram values of total cloud cover (clct) between 0 and 100% and pressure velocity at 500 hPa (omega500) between -1 and 1 Pa/s clc-qc-qi_data – cloud properties data; for the various simulations, cloud cover (clc), diagnostic specific humidity (tot_qv_dia), diagnostic cloud liquid mass mixing ratio (tot_qc_dia), and diagnostic cloud ice mass mixing ratio (tot_qi_dia) all as a function of time and height cloudclass_data – classifications of grid cells into cloud classes for different thresholds and all time steps of the various simulations cloudheating_for_cloudclass – for three sets of thresholds (hq60_mq60_lq25, hq62_mq67_lq30, hq65_mq70_lq35), time mean area mean cloud radiative heating rates (longwave, shortwave, and net) associated with different cloud classes as a function of height. hq n _mq m _lq o denotes a high cloud classification threshold of n %, a middle cloud classification threshold of m %, and a low cloud classification threshold of o % cloudprops_for_cloudclass - for three sets of thresholds (hq60_mq60_lq25, hq62_mq67_lq30, hq65_mq70_lq35), time mean area mean diagnostic cloud liquid mass mixing ratio, diagnostic cloud ice mass mixing ratio, and cloud cover as a function of height. hq n _mq m _lq o denotes a high cloud classification threshold of n %, a middle cloud classification threshold of m %, and a low cloud classification threshold of o % domain-mean_data – includes a land-sea mask for our simulation domain and period (201609-land-sea-mask.nc); ERA5 longwave (lw_crh), shortwave (sw_cr), and net cloud-radiative heating (nt_crh); external parameter file for our simulations (extpar_icon-grid_nawdex_78w40e23n80n_R5000m_bitmap.nc) occurrence_data – pickled data of cloud class occurrences, both with and without area weighting, for the various simulations openoceanmask – ocean mask (1 for ocean, 0 for land) for the various simulations q_data – time mean area mean diagnostic cloud liquid mass ...